GENDER DIVERSITY, FINANCIAL EXPERTISE, CEO DUALITY AND FIRM PERFORMANCE: Evidence from Indonesian Public Listed Companies - Wicaksono, Agung Prasetyo Nugroho (LP2M Institut Teknologi dan Bisnis Asia Malang, 2022)
This study aims to examine gender diversity, financial expertise, CEO duality on company performance in Indonesia. The author uses panel data testing with three years starting from 2018 - 2020 using STATA software. Panel data testing was carried out by conducting three tests: common effect model, fixed-effect model, and random effect model, including the model selection test, namely the Chow test, the Hausmann test, and the Breusch pagan LM test. The author also tested by conducting factor analysis with principal component analysis to carry out a linear transformation to change from most of the original variables used (ROA & ROE), and make them correlated into a new set of variables (firm performance). The results of this study conclude that the gender diversity variable has no effect on firm performance, but the variables of financial expertise and CEO duality affect firm performance.